Diseño geométrico e hidráulico del camino vecinal La Libertad de Huascayacu comunidad nativa San Rafael, distrito de Moyobamba, provincia de Moyobamba – San Martín - Sinarahua Tenazoa, Jhon Harold (2016)
In the last 17 years Peru has promoted a favorable policy for the construction of road works throughout the territory, according to reports from the Ministry of Transport and Communications having executed more than 15,000 kilometers of roads with asphalt pavements. The thesis project called "Geometric and Hydraulic Design Neighborhood Road Freedom Of Huascayacu - Native Community San Rafael, is aimed to provide a fast, economical and optimal solution for road improvement, because in many ways, neglect in drainage or lack thereof, causes them to deteriorate and present cracks, fissures, etc. causing discomfort to users, lack of communication between towns and cities, or in the worst case the total change folder rollThis project taking the definitive study of the soil, specifically by applying the USACE method gives a practical guide to prevent the deterioration of roads, ie lesser "time, with little manpower and equipment, and cheaper . To this end, it informs the basics, features and proper use of standards for the application of the tests of each of the components. Finally reached give a contribution on the application of said, for different projects in roadworks, so the results obtained for this thesis served to improve the road with criteria of strict quality control and especially the evolution of ground resistance according sub asphalt life progresses; as detailed in the laboratory analysis of soil mechanics, in preventing or loss of surface aggregates that can be set and especially the very strength of the mortar obtained for asphalt.